China Pakistan Economic Corridor - Aon , Muhammad; Amin , Muhammad; Akram, Ayesha (Advances in Social Sciences Research Journal, 2019)
The China Pakistan Economic Corridor (CPEC), a project of China’s Belt and Road Initiative (BRI), is being seen as a game changer for Pakistan that will connect china's south-western region Xinxiang, Tibet and Qinghai with Pakistan's southern part particularly Gwadar. This project will brings economic development and prosperity for whole south Asia. CPEC is a ready-made solution to Pakistan's many economic troubles. this economic corridor will run about 2700km from Gwadar to Kashgar By CPEC Pakistan will develop Gwadar port, link it to Karachi and Lahore through motorways and through karakaram highway to Kashgar in south-western china. CPEC is a joint project of Pakistan and Chinese government agreed to finance through Chinese investments utilizing investment loans largely by Chinese institutions. Pakistan will also invest 15 billion dollars on its own in the process. Through this Pakistan's trade will increase, transportation will become more efficient, constructing energy projects to improve its energy situation This mega project will enhance regional connectivity, develop infrastructure and easy way to contact people to people in both countries